2009
DOI: 10.2147/ijwh.s4957
|View full text |Cite
|
Sign up to set email alerts
|

Functional health literacy in Spanish-speaking Latinas seeking breast cancer screening through the National Breast and Cervical Cancer Screening Program

Abstract: Background:This analysis examines the association between functional health literacy and follow-up after mammography among women receiving breast cancer screening at a National Breast and Cervical Cancer Early Detection Program site in New York City that provides universal bilingual case management.Methods:A total of 707 Latinas who spoke Spanish as their primary language completed a survey of health and demographic characteristics and the Test of Functional Health Literacy in Spanish (TOFHLA-S). Survey result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…The articles include 4 studies of colorectal cancer screening (Table 1) [38-41], 5 studies of breast cancer screening (Table 2) [39, 42-45], 3 studies of cervical cancer screening (Table 3) [39, 42, 46], and 2 studies of prostate cancer screening (Table 4) [39, 47]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles include 4 studies of colorectal cancer screening (Table 1) [38-41], 5 studies of breast cancer screening (Table 2) [39, 42-45], 3 studies of cervical cancer screening (Table 3) [39, 42, 46], and 2 studies of prostate cancer screening (Table 4) [39, 47]. …”
Section: Resultsmentioning
confidence: 99%
“…One study included only women older than 65 years of age [43]. All studies offered at least part of the interview in Spanish or English [39, 42-45]. Three of the five studies offered the health literacy assessment in Spanish or English [42, 44, 45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient population is composed of predominantly female and foreign-born persons residing in northern Manhattan. Many patients are not fluent in English and have low literacy levels, even in their native language, 25 thus necessitating special measures to accommodate their particular language, educational, and literacy needs. Therefore, the NMCSP has historically provided face to face CRC education at the time of kit distribution by bilingual health educators, whose role is comparable to that of patient navigators in that they keep in contact with the patient until the screening test is complete, assess barriers, and provide counseling and education.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in California found persistent low health literacy among Hispanics with low English proficiency (Sentell, & Braun, 2012). Clinical-based studies conducted in North Carolina, New York, and California found high prevalence of low health literacy among male and female patients (Brice et al, 2008; Garbers, Schmitt, Rappa, & Chiasson, 2010; Sudore et al, 2009). One study with primary care patients on the U.S.-Mexico border found that more than 98% had adequate health literacy (Penaranda, Diaz, Noriega, & Shokar, 2012).…”
mentioning
confidence: 99%